Awareness and Impact of HIV/AIDS among the Teenagers in Ethiopia - Renjith Kumar, R.; G., Biju (Indian Journal of Marketing, 2009)
The aim of this research is to identify the awareness of HIV/AIDS message and its impact on the youngsters. This paper tries to explore whether they practically adopt the message. A sample of 400 students from grade 9 to 12 is selected at random for the study. The analysis shows that 47% of the students are influenced by HIV/AIDS message. 59% of the students are involved in sex with one person. It is proved that students aged above 19 years are involved in sexual relationship with one or more partners than the teenagers. 53% of the students do not know the status of HIV since they haven't tested so far or unable to recall the status. The HIV status of 5% of the sample is positive. It is concluded that HIV is positive more for males than females. Students aged 13-15 are HIV positive more than other age group students.